Opposing Oxytocin Effects on Intergroup Cooperative Behavior in Intuitive and Reflective Minds - Ma, Yina (Neuropsychopharmacology, 2015)
People often favor ingroup over outgroup members when choosing to cooperate. Such ingroup-favored cooperation is promoted by oxytocin—a neuropeptide shown to facilitate social cognition and that has emerged as a pharmacological target for treatments of social functioning deficits. The current study applied a dual-process model to investigate whether and how intuitive and reflective cognitive styles affect the oxytocin-motivated ingroup favoritism in cooperation. We examined oxytocin effects on ingroup favoritism in a double-blind, placebo-controlled between-subjects design where cognitive processing (intuition vs reflection) was experimentally manipulated in healthy Chinese males (n=150). We also supplemented this experimental manipulation with an individual difference analysis by assessing participants' inclination toward intuition or reflection in daily life. Intranasal administration of oxytocin (vs placebo) increased ingroup favoritism among participants primed to be intuitive or those who preferred intuition in daily life. In contrast, oxytocin decreased ingroup favoritism in participants primed to rely on reflective thinking or those who preferred reflective decision-making in daily life. Our results demonstrate that oxytocin has distinct functional roles when different cognitive styles (ie, intuition vs reflection) are promoted during social cooperation in a group situation. Our findings have implications for oxytocin pharmacotherapy of social dysfunction in that whether the effects of oxytocin on social functioning are facilitative, debilitative, or null, depends on an individual's cognitive style.